Managing the leachate at the regional landfill in Kikinda - Marković Sanja; Milanović Jelena (Trendovi u Poslovanju)
In developed, industrial countries, there is 1.2kg waste per capita, waste being collected and disposed of in regulated, sanitary landfills, which have systems for the protection of groundwater and air from pollutants, in Serbia, the largest number of landfills does not meet even the basic safety criteria for environmental protection. Several municipalities in Serbia began with the organization of the regional waste management system and within that frame, the construction of regional landfills which meet European standards in terms of environmental protection. The paper presents a method of management and use of leachate at the regional waste landfill 'ASA', Kikinda.